Sanksi Pidana Pelaku LGBT dalam Perspektif Fiqh Jinayah - Qomarauzzaman Qomarauzzaman (PSGA LP2M IAIN Pontianak, 2016)
Islam prohibits Lesbian, Gay, Bisexual, and Transgender because of ignoring the human nature. Thus, on Jinayah perspective (Islamic Criminal Law) the LGBT behaviors are categorised as Jarimah (Criminality), and the subjects of LGBT should be punished legally (‘uqubah). Furthermore, the classification of law on LGBT to create the justice related to Islam as a religion (hifdz al-dī), genetic issue (hifdz an-Nasl), intelligence (hifdz al-‘aql), soul (hifdz an-Nafs) and poverty (hifdz al-māl). Furthermore, based on Jinayah perspective, homosexual (al-Liwaṭh/as-Sihaq) is classified as jarimah zina so the subjects would be whipped a hundred times and isolated for one year (if the doer is ghairu muhshan). Then, if the subject is muhshan, he/she would be thrown by stones until death. Meanwhile, the bisexual people would be sanctioned by ta'zir; the government (uli al-‘amr) would decide the punishment.